1994
DOI: 10.1016/s0095-5108(18)30348-8
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Infectious Disease in Neonates

Abstract: There are many bacterial and viral pathogens that have been associated with enteric disease during the newborn period. These pathogens have widely different mechanisms of action on the intestinal epithelium and are associated with a spectrum of clinical findings. Infected infants can be asymptomatic, have gastroenteritis, or have a fulminant sepsis picture. To determine therapy and institute appropriate infection control measures requires the ability to recognize the clinical syndrome and correctly interpret l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…It has been suggested that immaturity of local intestinal defenses may contribute to the increased susceptibility of neonates to infections from luminal flora and to necrotizing enterocolitis (28,29). Therefore, we sought to more clearly characterize defensin expression in Paneth cells of the human small intestine, with a focus on fetal expression.…”
mentioning
confidence: 99%
“…It has been suggested that immaturity of local intestinal defenses may contribute to the increased susceptibility of neonates to infections from luminal flora and to necrotizing enterocolitis (28,29). Therefore, we sought to more clearly characterize defensin expression in Paneth cells of the human small intestine, with a focus on fetal expression.…”
mentioning
confidence: 99%
“…When the tissue COX protein content was determined, the newborn small bowel tissue had a significantly reduced COX-1 content than the adult. Interestingly, gastric lesions during endotoxemia are rarely seen clinically, as compared with the small bowel (1,2).…”
Section: Figmentioning
confidence: 99%
“…It is widely recognized that newborns are more susceptible to localized and disseminated infection than adults (1). This greater vulnerability early in life is in part related to the rather immature immunologic system of the neonate.…”
mentioning
confidence: 99%